A Consideration of Literature on Trust and Distrust as they Relate to Auditor Professional Scepticism. Issue 3 (1st July 2016) - Harding, Noel; Azim, Mohammad I.; Jidin, Radzi; Muir, Janine P.
Abstract : With a view to expanding the discussion on professional scepticism, and motivating a broader perspective in research undertaken with the aim of helping auditors meet ongoing demands for an elevated level of professional scepticism, we consider the literature on trust and distrust as it relates to auditor professional scepticism. We draw on literature from a range of disciplines, and highlight new opportunities and previously unidentified challenges in helping auditors exercise an elevated level of professional scepticism. We distinguish between trust and distrust and note that the issue of professional scepticism is likely to be as much about auditors being insufficiently distrusting as it is about auditors being overly trusting. A number of potentially fruitful means by which professional scepticism might be enhanced are highlighted but we also encourage caution in that lower levels of trust in management, and increased distrust in management, may have unintended negative consequences.